NILAI KESANTUNAN DALAM TRADISI KEMPONAN: STUDI ETNOPRAGMATIK MASYARAKAT MELAYU PONTIANAK - Ramaniyar, Eti; Wiranty, Wiendi (SEBASA Jurnal Pendidikan Bahasa dan Sastra, 2026)
This research is motivated by the phenomenon of kemponan that continues to exist in the Malay community of Pontianak, understood not merely as a traditional belief but as a manifestation of politeness within the local speech culture. The study aims to describe the community’s perception of the kemponan concept, portray informants’ experiences in encountering or observing the practice, and explain how the meaning of politeness is interpreted through it. A qualitative descriptive method was employed, using in-depth interviews and observations of kemponan practices in Pontianak’s social context. The findings reveal that kemponan is perceived as a form of respect toward the giver and as a means of maintaining social harmony. This practice functions as a guideline for polite behavior in daily interactions and reflects pragmatic politeness values rooted in Malay local wisdom. Thus, kemponan serves not only as a cultural tradition but also as an expression of linguistic ethics and a strategy for preserving social balance within the Pontianak Malay community.